Living standards in black and white: evidence from the heights of Ohio prison inmates, 1829 - 1913 - Scott Alan Carson; Thomas N. Maloney (Center for Economic Studies and ifo Institute (CESifo), 2006)
The use of height data to measure living standards is now a well-established method in the economic history literature. Moreover, a number of core findings in this literature are widely agreed upon. There are still some populations, places, and times, however, for which anthropometric evidence remains thin. One example is African-Americans in the Northern US in the 1800s. Here, we use new data from the state prison in Ohio to track heights of black and white men from 1829 to 1913. We corroborate the well-known mid-century height decline among white men in Ohio, found by Steckel and Haurin (1994) using National Guard data. We find that black men in Ohio were shorter than white men, throughout the century and controlling for a number of characteristics. We also find a pattern of height decline in midcentury similar to that found for white men.
Keywords: I12; I31; I32; J15; N31; 330